Higher order Kantorovich-type Szasz-Mirakjan operators - Sabancigil, Pembe; Kara, Mustafa; Mahmudov, Nazim, I (Springer, 2022)
In this paper, we define new higher order Kantorovich-type Szasz-Mirakjan operators, we give some approximation properties of these operators in terms of various moduli of continuity. We prove a local approximation theorem, a Korovkin-type theorem, and a Voronovskaja-type theorem. We also prove weighted approximation theorems for these new operators.
Keywords: Modulus of continuity; Higher order approximation; Szasz-Mirakjan operators; Kantorovich operators; Voronovskaja-type theorem